(untitled) (Journal of actual problems of jurisprudence, 2018)
This article is devoted to research of the traces left by the person on a place of commission of crime. Classification of these traces is carried out. In article the practical materials taken from criminal cases from archive of specialized interdistrict court of Almaty on criminal cases are used. The conclusion that only complex use of the advanced achievements of criminalistic science and the latest criminalistic equipment at detection, withdrawal, fixing, research and use of traces, promotes observance of the rights and freedoms of the person and citizen guaranteed by the Constitution and enshrined in international treaties is drawn. Also it increases quality of pre-judicial investigation on criminal cases. It in turn is the main prerequisite of ensuring inevitability of reaction of the state to any offenses, strict following to the principle of «zero tolerance (tolerance)» to offenses. Key words. Criminalistics, traces of crimes, human rights, crime, identification, object of a crime, criminal case.